Інституціоналізація діагностики і розвитку управлінських та лідерських здібностей публічних службовців – пріоритетний напрямок реформування державної служби та служби в органах місцевого самоврядування в Україні - Федоренко, В.; Fedorenko, V. (Східноєвропейський національний університет імені Лесі Українки, 2015)
Стаття присвячена проблемам теорії та практики виявлення та розвитку професійно важливих управлінських і лідерських здібностей державних службовців і службовців органів місцевого самоврядування в умовах реформи публічної служби, започаткованої в Україні в 2014-2015 рр. Досліджуються перспективи унормування в новому Законі «Про державну службу» тестування, щорічної оцінки та інших інструментів виявлення та розвитку управлінського і лідерського потенціалу публічних службовців. Обгрунтовується концепт розробки і запровадження відповідного навчального модуля в магістерські програми з публічного управління та адміністрування в Україні. The article is devoted to the Theory and practice of identification of professional and important management and leadership skills of public servants and employees of local governments in terms of public service reform, launched in Ukraine in 2014 -2015. IT IS the study of the perspectives rationed in the new law «On civil service» which introduces testing, annual assessment and other instruments of identification and development of managerial and leadership potential of public officials. The article tackles the concept of development and implementation of appropriate training module in the master's program on public management and administration in Ukraine. Important competencies to be formed in masters and doctoral students of public administration are: understanding the nature and content of professionally important management and leadership skills that need to be identified and developed in public officials; knowledge of the basic forms and methods of identifying managerial and leadership skills which are used today in Ukraine and abroad; being able to interview and test the candidate; knowledge of case-studies technology and other forms of diagnosing management and leadership skills of the candidates for the posts in the public establishments; awareness of the goals and objectives of management and leadership skills of public officials; knowledge of basic techniques of leadership skills development among public officials, especially in higher ranks of public service; to posses skills of testing, structuring interviews, conducting workshops, organizing assistant centers and other innovative forms of developing management and leadership skills of public servants.
Institutionalization of Diagnosing the Management and Leadership Skills of Public Officials - the Prior Direction of Reforming the Civil Service and Local Governments in Ukraine.
Keywords: державна служба; служба в органах місцевого самоврядування; лідерство; реформа публічної служби; Закон «Про державну службу»; діагностика та розвиток управлінських і лідерських здібностей; тестування; співбесіда; public service; service in local government; leadership; public service reform; the new law «On civil service»; diagnosis and development of management and leadership skills; testing; interview